2017
DOI: 10.1016/j.tibs.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Mechanism of Group II Intron Splicing

Abstract: While the major architectural features and active-site components of group II introns have been known for almost a decade, information on individual stages of splicing has been lacking. Recent advances in crystallography and cryo-electron microscopy have provided major new insights into the structure of intact lariat introns. Conformational changes that mediate the steps of splicing and retrotransposition are being elucidated, revealing the dynamic, highly coordinated motions that are required for group II int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 71 publications
(182 reference statements)
0
57
0
Order By: Relevance
“…Phosphorothioate substitution studies showed that U6 catalyzes both steps of pre-mRNA splicing by positioning two Mg 2+ ions that stabilize the leaving groups during each reaction (Fica et al 2013). The active site RNA conformations of the spliceosome and group II introns are highly similar (Zhao and Pyle 2017), but the former requires proteins for its formation and stabilization as described below.…”
Section: Resmentioning
confidence: 99%
“…Phosphorothioate substitution studies showed that U6 catalyzes both steps of pre-mRNA splicing by positioning two Mg 2+ ions that stabilize the leaving groups during each reaction (Fica et al 2013). The active site RNA conformations of the spliceosome and group II introns are highly similar (Zhao and Pyle 2017), but the former requires proteins for its formation and stabilization as described below.…”
Section: Resmentioning
confidence: 99%
“…The group II intron RNA secondary structure consists of six double-helical domains, DI to DVI, with DI, DV and DVI playing essential roles in splicing (Figure 1B) [1, 35]. DI is the largest domain and forms a structural scaffold for the molecule and also contains the exon recognition elements (exon binding sites, EBSs) [2, 68]. DV is the most highly conserved domain and contains the so-called “catalytic triad” (usually AGC, but often CGC), which binds catalytically important Mg 2+ ions and, in combination with parts of DI, forms the active site.…”
Section: Group II Introns Are Ribozymes and Mobile Genetic Elementsmentioning
confidence: 99%
“…IEPs are multifunctional proteins containing conserved RT domains as well as a domain X associated with RNA binding and maturase activity involved in splicing. There are also DNA binding and DNA endonuclease domains involved in mobility (Figure 1) [1–4, 8]. …”
Section: Group II Introns Are Ribozymes and Mobile Genetic Elementsmentioning
confidence: 99%
“…Group I introns, widely present in mRNA, rRNA and tRNA of variety of organisms including algae, fungi, lower eukaryotes and few bacteria [38][39][40][41][42]. Similarly, group II introns are large autocatalytic ribozymes widely present in the mitochondria, chloroplast, plants, fungi, yeast and many bacteria, play major role in genome evolution [43][44][45][46]. The tRNA introns widely present in all domains of life are exceptionally different as enzymes are involved in the removal of intron and in the joining of the two halves [47][48][49].…”
Section: Intronic Regionsmentioning
confidence: 99%